Follistatin Effects in Migration, Vascularization, and Osteogenesis in vitro and Bone Repair in vivo - Fahmy-Garcia, Shorouk; Farrell, Eric; Witte-Bouma, Janneke; Robbesom-van den Berge, Iris; Suarez, Melva; Mumcuoglu, Didem; Walles, Heike; Kluijtmans, Sebastiaan G. J. M.; van der Eerden, Bram C. J.; van Osch, Gerjo J. V. M.; van Leeuwen, Johannes P. T. M.; van Driel, Marjolein (Frontiers in Bioengineering and Biotechnology, 2019)
The use of biomaterials and signaling molecules to induce bone formation is a promising approach in the field of bone tissue engineering. Follistatin (FST) is a glycoprotein able to bind irreversibly to activin A, a protein that has been reported to inhibit bone formation. We investigated the effect of FST in critical processes for bone repair, such as cell recruitment, osteogenesis and vascularization, and ultimately its use for bone tissue engineering. In vitro, FST promoted mesenchymal stem cell (MSC) and endothelial cell (EC) migration as well as essential steps in the formation and expansion of the vasculature such as EC tube-formation and sprouting. FST did not enhance osteogenic differentiation of MSCs, but increased committed osteoblast mineralization. In vivo, FST was loaded in an in situ gelling formulation made by alginate and recombinant collagen-based peptide microspheres and implanted in a rat calvarial defect model. Two FST variants (FST288 and FST315) with major differences in their affinity to cell-surface proteoglycans, which may influence their effect upon in vivo bone repair, were tested. In vitro, most of the loaded FST315 was released over 4 weeks, contrary to FST288, which was mostly retained in the biomaterial. However, none of the FST variants improved in vivo bone healing compared to control. These results demonstrate that FST enhances crucial processes needed for bone repair. Further studies need to investigate the optimal FST carrier for bone regeneration.